Self-supporting dual-function electro-catalytic material as well as preparation method and application thereof
By preparing three-dimensional composite materials, including three-dimensional Ni nanoframework and NiMoFe nanoalloy layer, the problem of insufficient catalytic electrode activity and stability in the prior art is solved, efficient water decomposition catalysis is achieved, and the risks and costs of the preparation process are reduced.
Patent Information
- Application Number
- CN202311121403.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-31
AI Technical Summary
It is difficult to develop dual-function catalytic electrodes with high catalytic activity and high stability in the prior art. Especially in water decomposition reactions, the preparation process of nanocatalytic materials is complicated, with safety risks and high energy consumption.
By preparing a three-dimensional composite material, including a three-dimensional Ni nanoframework and a NiMoFe nano alloy layer coated thereon, a self-supporting dual-function electrocatalytic material is formed. This material is prepared by electroplating method, and electroplating is performed using a mixed solution of nickel salt, molybdenum salt, iron salt and complexing agent to form an electrocatalytic material with a high specific surface area and characteristic peaks.
The electrolytic water catalytic material has high catalytic activity and high stability, and can be used as an efficient hydrogen evolution electrode and an oxygen evolution electrode, reducing safety hazards and energy consumption in the preparation process.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of catalyst preparation, and in particular, to a self-supporting dual-functional electrocatalytic material and a preparation method and application thereof. Background Art
[0002] Developing clean renewable energy is one of the effective ways to solve the problems of global warming and the decreasing fossil fuels. Converting solar and wind energy into transportable and storable chemical fuels is considered to be a very feasible solution. Hydrogen has the advantages of high gravimetric energy density, high abundance and cleanliness, and is a high-quality carrier of sustainable energy. Water decomposition is an important way to produce high-purity hydrogen. In order to overcome the high potential barrier of the water decomposition reaction, it is necessary to design and optimize the electrocatalysts of the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) half reactions. Precious metals are extremely active in water decomposition, but their scarcity still greatly hinders their large-scale application. Therefore, it is very meaningful to develop catalysts for HER and OER that are abundant, low-priced, efficient and stable, and have good market prospects.
[0003] Transition metals are one of the most widely used catalysts for catalytic water decomposition in alkaline media. Nanometal elements have poor electrochemical activity and stability due to problems such as size and surface electronic structure, which further limits their application in overall water decomposition. The performance can be improved by adjusting the structure of active sites through alloying, coating or compounding. For example, Ho et al. (Nano Energy, 2016, 27, 247-254) reported the application of nickel-molybdenum alloy nanomaterials in hydrogen evolution reaction. The catalyst has good HER catalytic activity, but the preparation process uses 20% concentration of hydrogen at high temperature, which poses a great safety hazard. Xv et al. (Adv. Mater. 2017, 29, 1605957) reported a nitrogen-doped carbon-coated nickel nanoparticle as a water electrolysis catalyst, but the high-temperature carbonization preparation process at 800°C brought high energy consumption, and the hydrogen evolution overpotential of the material was large; Zhou et al. (Chem. Eng. J. 2020, 394, 124977) reported a nickel-iron alloy based on nitrogen-doped carbon material, which has better water decomposition activity than single-element doped carbon composite materials, but the binder made into electrodes also caused a decrease in active area. It can be seen that most of the highly active self-supporting nanocatalytic materials are prepared under complex and harsh conditions, and more nanocatalytic materials on the market are in powder form, which need to be made into electrodes with polymer binders, resulting in a reduction in active surface area and a decrease in charge transfer efficiency, resulting in a higher overpotential and the possibility of stratification at high current density. In addition, in industrial applications, it is difficult to obtain a dual-functional catalytic electrode with both high catalytic activity and high stability. Summary of the invention
[0004] The purpose of the present disclosure is to provide a self-supporting bifunctional electrocatalytic material and a preparation method and application thereof. The electrocatalytic material has the advantages of high catalytic activity and high stability, and the electrocatalytic material has bifunctionality and can be used as a hydrogen evolution electrode and an oxygen evolution electrode.
[0005] In order to achieve the above objectives, the first aspect of the present disclosure provides a self-supporting bifunctional electrocatalytic material, which includes a three-dimensional composite material, wherein the three-dimensional composite material includes a three-dimensional Ni nanoskeleton and a NiMoFe nanoalloy layer coated on the three-dimensional Ni nanoskeleton.
[0006] Optionally, the BET specific surface area of the electrocatalytic material is 2.1 to 2.9 m 2 / g, preferably 2.3 to 2.7 m 2 / g; in the XRD diagram of the electrocatalytic material, there are characteristic peaks at 2θ of 37-40°, 40-43°, 44-47°, 55-60°, 70-74° and 75-80°; XPS measures that the atomic content of Ni element in the electrocatalytic material is 58-84%, the atomic content of Mo element is 9-29%, and the atomic content of Fe element is 4-26%.
[0007] Optionally, the NiMoFe nano alloy layer has a thickness of 10 to 50 nm.
[0008] Optionally, the electrocatalytic material also includes a conductive substrate, and the three-dimensional composite material is coated on the conductive substrate; the conductive substrate is a flexible conductive substrate or a hard conductive substrate; the flexible conductive substrate is one of carbon cloth or foam metal; the foam metal is selected from one of foam nickel and foam copper; the hard conductive substrate is one of carbon paper or conductive glass.
[0009] The second aspect of the present disclosure provides a method for preparing the electrocatalytic material according to the first aspect of the present disclosure, the method comprising:
[0010] S1: mixing nickel salt, molybdenum salt, iron salt and a complexing agent to obtain a mixed solution; adjusting the mixed solution to alkaline using a pH regulator to obtain an electrolyte;
[0011] S2: Using the three-dimensional Ni nano-skeleton as a working electrode, placing it in the electrolyte obtained in S1, and performing electroplating.
[0012] Optionally, the nickel salt in step S1 is selected from one or more of nickel chloride, nickel sulfate and nickel nitrate, preferably nickel chloride; the molybdenum salt is selected from one or more of sodium molybdate, potassium molybdate and ammonium molybdate, preferably sodium molybdate; the iron salt is selected from one or more of ferrous sulfate and ferrous chloride, preferably ferrous sulfate; the chelating agent is selected from one or more of sodium citrate, potassium citrate, ethylenediaminetetraacetic acid and disodium ethylenediaminetetraacetic acid, preferably sodium citrate.
[0013] Optionally, in step S1, the mass ratio of the nickel salt, the molybdenum salt, the iron salt and the complexing agent is 1: (0.03-0.25): (0.03-0.25): (0.35-1.50), preferably 1: (0.06-0.13): (0.06-0.13): (0.45-0.75);
[0014] The concentration of the nickel salt is 0.04-0.08 g / ml; the concentration of the molybdenum salt is 0.002-0.01 g / ml; the concentration of the iron salt is 0.002-0.01 g / ml; the concentration of the complexing agent is 0.03-0.06 g / ml;
[0015] Step S1 also includes adjusting the pH of the mixed solution to above 9 using a pH adjuster; the pH adjuster includes one or more of sodium carbonate, sodium hydroxide and potassium hydroxide, preferably sodium carbonate.
[0016] Optionally, in step S2, the electroplating conditions include: a current density of 50 to 300 mA / cm 2 , preferably 100 to 200 mA / cm 2 ; The electroplating time is 200 to 600 seconds, preferably 300 to 560 seconds; the reference electrode is one or more of a silver chloride electrode, a mercury / mercury oxide electrode and a saturated calomel electrode, preferably a silver chloride electrode; the counter electrode is one or more of a platinum wire and a carbon rod, preferably a platinum wire.
[0017] Optionally, the cross-sectional diameter of the three-dimensional Ni nano-skeleton is 90-120 nm, and the BET specific surface area is 2.7-2.9 m 2 / g; in the XRD pattern of the three-dimensional Ni nanoskeleton, there are characteristic peaks at 2θ of 37-40°, 40-43°, 44-47°, 55-60°, 70-74° and 75-80°.
[0018] Optionally, the three-dimensional Ni nanoframe is prepared by the following method:
[0019] A nickel hydroxide nano-precursor is prepared on a conductive substrate; and the nickel hydroxide nano-precursor is calcined in a reducing atmosphere.
[0020] Optionally, the reducing atmosphere is a mixed gas containing hydrogen and an inert gas; the volume fraction of the hydrogen is 2% to 8%;
[0021] The calcination conditions include: a calcination temperature of 300 to 500° C. and a calcination time of 0.5 to 2 hours.
[0022] The third aspect of the present disclosure provides use of the electrocatalytic material prepared by the method described in the second aspect of the present disclosure in an oxygen evolution electrode or a hydrogen evolution electrode for electrolysis of water.
[0023] Through the above technical scheme, the present invention prepares a NiMoFe nano alloy layer and coats a three-dimensional Ni nano skeleton to obtain a self-supporting bifunctional electrocatalytic material, thereby achieving the advantages of high catalytic activity and high stability of the water electrolysis catalytic material. The electrocatalytic material has bifunctionality and can be used as a high-efficiency hydrogen evolution electrode and oxygen evolution electrode.
[0024] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0026] Figure 1 This is a scanning electron microscope (SEM) image of the electrocatalytic material obtained in Example 1 of the present application.
[0027] Figure 2 This is the X-ray diffraction (XRD) diagram of the electrocatalytic material obtained in Example 1 of the present application. DETAILED DESCRIPTION
[0028] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0029] A first aspect of the present disclosure provides a self-supporting bifunctional electrocatalytic material, wherein the electrocatalytic material comprises a three-dimensional composite material, wherein the three-dimensional composite material comprises a three-dimensional Ni nano-skeleton and a NiMoFe nano-alloy layer coated on the three-dimensional Ni nano-skeleton.
[0030] The self-supporting bifunctional electrocatalytic material disclosed in the present invention exhibits good catalytic activity and catalytic stability in hydrogen evolution and oxygen evolution reactions in water electrolysis.
[0031] According to an embodiment of the present disclosure, in the XRD graph of the electrocatalytic material, there are characteristic peaks at 2θ of 37-40°, 40-43°, 44-47°, 55-60°, 70-74° and 75-80°; XPS measures that the atomic content of Ni element in the electrocatalytic material is 58-84%, the atomic content of Mo element is 9-29%, and the atomic content of Fe element is 4-26%. The XPS test results are the content of each element on the surface of the test electrocatalytic material.
[0032] According to one embodiment of the present disclosure, the BET specific surface area of the electrocatalytic material is 2.1 to 2.9 m 2 / g, preferably 2.3 to 2.7 m 2 / g.
[0033] According to an embodiment of the present disclosure, the thickness of the NiMoFe nano alloy layer is 10 to 50 nm. The above embodiment is conducive to the electrocatalytic material showing good catalytic activity and catalytic stability in the hydrogen evolution and oxygen evolution reactions in water electrolysis.
[0034] According to one embodiment of the present disclosure, the electrocatalytic material also includes a conductive substrate, and the three-dimensional composite material is coated on the conductive substrate; the conductive substrate is a flexible conductive substrate or a hard conductive substrate; the flexible conductive substrate is one of carbon cloth or foam metal; the foam metal is selected from one of foam nickel and foam copper; the hard conductive substrate is one of carbon paper or conductive glass (FTO).
[0035] The second aspect of the present disclosure provides a method for preparing the electrocatalytic material according to the first aspect of the present disclosure, the method comprising:
[0036] S1: mixing nickel salt, molybdenum salt, iron salt and a complexing agent to obtain a mixed solution; adjusting the mixed solution to alkaline using a pH regulator to obtain an electrolyte;
[0037] S2: Using the three-dimensional Ni nano-skeleton as a working electrode, placing it in the electrolyte obtained in S1, and performing electroplating.
[0038] According to one embodiment of the present disclosure, the nickel salt in step S1 is selected from one or more of nickel chloride, nickel sulfate and nickel nitrate, preferably nickel chloride; the molybdenum salt is selected from one or more of sodium molybdate, potassium molybdate and ammonium molybdate, preferably sodium molybdate; the iron salt is selected from one or more of ferrous sulfate and ferrous chloride, preferably ferrous sulfate; the complexing agent is selected from one or more of sodium citrate, potassium citrate, ethylenediaminetetraacetic acid and disodium ethylenediaminetetraacetic acid, preferably sodium citrate. In a further embodiment, the mass ratio of the nickel salt, the molybdenum salt, the iron salt and the complexing agent in step S1 is 1: (0.03-0.25): (0.03-0.25): (0.35-1.50), preferably 1: (0.06-0.13): (0.06-0.13): (0.45-0.75); the concentration of the nickel salt is 0.04-0.08 g / ml, preferably 0.05-0.10 g / ml. The concentration of the molybdenum salt is 0.002-0.01 g / ml, preferably 0.005-0.009 g / ml; the concentration of the iron salt is 0.002-0.01 g / ml, preferably 0.005-0.008 g / ml; the concentration of the complexing agent is 0.03-0.06 g / ml, preferably 0.045-0.055 g / ml. The above-mentioned embodiment is conducive to obtaining an electrocatalytic material with a good surface structure, so that the electrocatalytic material has a high electrochemical active area and good electrical conductivity, which is conducive to the conduction of electrons between the three-dimensional Ni nano-skeleton and the conductive substrate, and further conducive to the electrocatalytic material in the electrolysis of water hydrogen evolution and oxygen evolution reaction to show good catalytic activity and catalytic stability, thereby improving the catalytic performance.
[0039] According to an embodiment of the present disclosure, step S1 also includes using a pH regulator to adjust the pH of the mixed solution to above 9; the pH regulator includes one or more of sodium carbonate, sodium hydroxide and potassium hydroxide, preferably sodium carbonate. The above embodiment is conducive to obtaining an electrocatalytic material with a good surface structure, so that the electrocatalytic material has a high electrochemical active area and good conductivity, which is conducive to the conduction of electrons between the three-dimensional Ni nanoskeleton and the conductive substrate, and further helps the electrocatalytic material to show good catalytic activity and catalytic stability in the electrolysis of water for hydrogen evolution and oxygen evolution reactions, thereby improving the catalytic performance.
[0040] According to an embodiment of the present disclosure, in step S2, the electroplating conditions include: a current density of 50 to 300 mA / cm 2 , preferably 100 to 200 mA / cm 2; The electroplating time is 200-600s, preferably 300-560s; The reference electrode is one or more of a silver chloride electrode, a mercury / mercury oxide electrode and a saturated calomel electrode, preferably a silver chloride electrode; The counter electrode is one or more of a platinum wire and a carbon rod, preferably a platinum wire. The above-mentioned implementation is conducive to obtaining an electrocatalytic material with a good surface structure, so that the electrocatalytic material has a high electrochemical active area and good electrical conductivity, which is conducive to the conduction of electrons between the three-dimensional Ni nanoskeleton and the conductive substrate, and further conducive to the electrocatalytic material in the electrolysis of water hydrogen evolution and oxygen evolution reaction to show good catalytic activity and catalytic stability, thereby improving the catalytic performance.
[0041] According to one embodiment of the present disclosure, the cross-sectional diameter of the three-dimensional Ni nano-skeleton is 90-120 nm, and the BET specific surface area is 2.7-2.9 m 2 / g; in the XRD diagram of the three-dimensional Ni nano-skeleton, there are characteristic peaks at 2θ of 37-40°, 40-43°, 44-47°, 55-60°, 70-74° and 75-80°. The above-mentioned implementation mode is conducive to obtaining an electrocatalytic material with a better surface structure, so that the electrocatalytic material has a higher electrochemical active area and good electrical conductivity, which is conducive to the conduction of electrons between the three-dimensional Ni nano-skeleton and the conductive substrate, and is further conducive to the electrocatalytic material in the electrolysis of water hydrogen evolution and oxygen evolution reaction to show good catalytic activity and catalytic stability, thereby improving the catalytic performance.
[0042] According to one embodiment of the present disclosure, the three-dimensional Ni nano-skeleton is prepared by the following method: preparing a nickel hydroxide nano-precursor on a conductive substrate; calcining the nickel hydroxide nano-precursor under a reducing atmosphere. In a further embodiment, the reducing atmosphere is a mixed gas containing hydrogen and an inert gas; the volume fraction of the hydrogen is 2% to 8%; the calcination conditions include: a calcination temperature of 300 to 500°C, preferably 350 to 450°C, and a calcination time of 0.5 to 2h. The above-mentioned embodiment is conducive to obtaining an electrocatalytic material with a better surface structure, so that the electrocatalytic material has a higher electrochemical active area and good conductivity, which is conducive to the conduction of electrons between the three-dimensional Ni nano-skeleton and the conductive substrate, and is further conducive to the electrocatalytic material in the electrolysis of water hydrogen evolution and oxygen evolution reaction to show good catalytic activity and catalytic stability, thereby improving the catalytic performance.
[0043] The third aspect of the present disclosure provides use of the electrocatalytic material prepared by the method described in the second aspect of the present disclosure in an oxygen evolution electrode or a hydrogen evolution electrode for electrolysis of water.
[0044] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.
[0045] Unless otherwise specified, the reagents used in the examples and comparative examples are all commercially available products.
[0046] The BET test was performed on an instrument model SA3100.
[0047] XRD was performed on a Philips PW 1830 instrument.
[0048] XPS was performed on a PHI 5600 instrument.
[0049] SEM was performed on a JSM-6700F instrument.
[0050] The electrochemical performance was carried out on a CHI 760D electrochemical workstation.
[0051] Example 1
[0052] (1) placing a conductive substrate carbon cloth into a glass container containing 15 mL of 0.125 mol / L nickel chloride hexahydrate and 0.25 mol / L hexamethylenetetramine aqueous solution, sealing the glass container with a plastic cover, and placing the glass container in an oven at 100° C. for 10 hours to obtain a nickel hydroxide precursor;
[0053] (2) washing the nickel hydroxide precursor grown on the carbon cloth with distilled water and ethanol, and drying it in a vacuum oven at 80°C for 120 min. The dried product was transferred to a tube furnace, heated to 400°C at a heating rate of 5°C / min, and calcined for 1 h in a reducing atmosphere, wherein the reducing atmosphere was a mixed gas of hydrogen and nitrogen (the volume fraction of hydrogen was 5.0%), to obtain a three-dimensional Ni nanoskeleton;
[0054] (3) 2.3 g of nickel chloride hexahydrate, 0.2 g of sodium molybdate dihydrate, 0.16 g of ferrous sulfate heptahydrate and 1.7 g of sodium citrate dihydrate were dissolved in 30 mL of distilled water, and the pH value of the solution was adjusted to above 9 with sodium carbonate to obtain an electrolyte; the mass ratio of the nickel salt, the molybdenum salt, the iron salt and the complexing agent was 1:0.087:0.069:0.74, and the concentration of the nickel salt was 0.077 g / ml; the concentration of the molybdenum salt was 0.0067 g / ml; the concentration of the iron salt was 0.0053 g / ml; and the concentration of the complexing agent was 0.0567 g / ml;
[0055] (4) The three-dimensional Ni nanoframe obtained in step (2) was used as a working electrode and placed in the electrolyte obtained in step (3) for electroplating, with a silver chloride electrode as a reference electrode and a platinum wire as a counter electrode at 160 mA / cm 2 The electrodeposition was carried out for 480 s at a constant current of , and the obtained product was washed with distilled water several times and dried in a vacuum oven at 30°C to obtain an electrocatalytic material.
[0056] According to the test analysis of XRD, SEM and XPS, the atomic content of Ni element on the surface of the electrocatalytic material is 76%, the atomic content of Mo element is 15%, the atomic content of Fe element is 9%, and the BET specific surface area of the electrocatalytic material is 2.6m 2 / g; in the XRD pattern, there are characteristic peaks at 2θ of 26°, 38°, 41°, 44°, 58°, 72° and 78°, which are attributed to the three-dimensional Ni nanoskeleton in the electrocatalytic material; the cross-sectional diameter of the three-dimensional Ni nanoskeleton is 100nm, and the BET specific surface area is 2.7m 2 / g; the thickness of the NiMoFe nano alloy layer is 20nm.
[0057] Example 2
[0058] The method of this embodiment is the same as that of embodiment 1, except that:
[0059] 2.3 g of nickel chloride hexahydrate, 0.4 g of sodium molybdate dihydrate, 0.32 g of ferrous sulfate heptahydrate and 1.7 g of sodium citrate dihydrate used in step (3) are dissolved in 30 mL of distilled water; the mass ratio of the nickel salt, the molybdenum salt, the iron salt and the complexing agent is 1:0.17:0.14:0.74, and the concentration of the nickel salt is 0.077 g / ml; the concentration of the molybdenum salt is 0.013 g / ml; the concentration of the iron salt is 0.011 g / ml; and the concentration of the complexing agent is 0.0567 g / ml.
[0060] The test analysis of XRD, SEM and XPS showed that the mass content of Ni element on the surface of the electrocatalytic material was 77%, the mass content of Mo element was 13%, the mass content of Fe element was 10%, and the BET specific surface area of the electrocatalytic material was 2.5 m 2 / g; in the XRD graph, there are characteristic peaks at 2θ of 26°, 38°, 41°, 44°, 58°, 72° and 78°; the cross-sectional diameter of the three-dimensional Ni nanoskeleton is 100nm, and the BET specific surface area is 2.7m 2 / g; the thickness of the NiMoFe nano alloy layer is 25nm.
[0061] Example 3
[0062] The method of this embodiment is the same as that of embodiment 1, except that:
[0063] 2.3 g of nickel chloride hexahydrate, 0.1 g of sodium molybdate dihydrate, 0.08 g of ferrous sulfate heptahydrate and 0.85 g of sodium citrate dihydrate used in step (3) are dissolved in 30 mL of distilled water; the mass ratio of the nickel salt, the molybdenum salt, the iron salt and the complexing agent is 1:0.043:0.035:0.37, and the concentration of the nickel salt is 0.077 g / ml; the concentration of the molybdenum salt is 0.003 g / ml; the concentration of the iron salt is 0.003 g / ml; and the concentration of the complexing agent is 0.028 g / ml.
[0064] The test analysis of XRD, SEM and XPS showed that the mass content of Ni element on the surface of the electrocatalytic material was 84%, the mass content of Mo element was 10%, the mass content of Fe element was 6%, and the BET specific surface area of the electrocatalytic material was 2.3 m 2 / g; in the XRD graph, there are characteristic peaks at 2θ of 26°, 38°, 41°, 44°, 58°, 72° and 78°; the cross-sectional diameter of the three-dimensional Ni nanoskeleton is 100nm, and the BET specific surface area is 2.7m 2 / g; the thickness of the NiMoFe nano alloy layer is 25nm.
[0065] Example 4
[0066] The method of this embodiment is the same as that of embodiment 1, except that in step (4), the constant current is 60 mA / cm 2 , the electrodeposition time is 240s.
[0067] The test analysis of XRD, SEM and XPS showed that the mass content of Ni element on the surface of the electrocatalytic material was 79%, the mass content of Mo element was 15%, the mass content of Fe element was 6%, and the BET specific surface area of the electrocatalytic material was 2.6 m 2 / g; in the XRD graph, there are characteristic peaks at 2θ of 26°, 38°, 41°, 44°, 58°, 72° and 78°; the cross-sectional diameter of the three-dimensional Ni nanoskeleton is 100nm, and the BET specific surface area is 2.7m 2 / g; the thickness of the NiMoFe nano alloy layer is 10nm.
[0068] Example 5
[0069] The method of this embodiment is the same as that of embodiment 1, except that in step (4), the constant current is 360 mA / cm 2 , the electrodeposition time is 80s.
[0070] The test analysis of XRD, SEM and XPS shows that the mass content of Ni element on the surface of the electrocatalytic material is 75%, the mass content of Mo element is 10%, the mass content of Fe element is 15%, and the BET specific surface area of the electrocatalytic material is 2.4m 2 / g; in the XRD graph, there are characteristic peaks at 2θ of 26°, 38°, 41°, 44°, 58°, 72° and 78°; the cross-sectional diameter of the three-dimensional Ni nanoskeleton is 100nm, and the BET specific surface area is 2.7m 2 / g; the thickness of the NiMoFe nano alloy layer is 15nm.
[0071] Comparative Example 1
[0072] The method of this comparative example is the same as that of Example 1, except that only steps (1) and (2) in Example 1 are performed in this comparative example to obtain a three-dimensional Ni nano-skeleton. The cross-sectional diameter of the three-dimensional Ni nano-skeleton is 100 nm, and the BET specific surface area is 2.7 m 2 / g.
[0073] Comparative Example 2
[0074] (1) Clean the nickel mesh with dilute hydrochloric acid, ethanol, and ultrapure water and use it as the cathode. Use the platinum sheet as the anode and prepare 0.1M Ni(Cl) 2 and 2M NH 4 Cl solution was placed in a beaker as an electrolyte. The positive and negative electrodes of a DC power supply were connected to a platinum sheet and a nickel mesh, respectively, and installed in the beaker so that the solution submerged the electrodes. At room temperature, the current density was set to 3 A / cm 2 , electrodeposition treatment for 90 seconds;
[0075] (2) dissolving 2.3 g of nickel chloride hexahydrate, 0.16 g of ferrous sulfate heptahydrate, and 1.7 g of sodium citrate dihydrate in 30 mL of distilled water, and adjusting the pH value of the solution to above 9 with sodium carbonate to obtain an electrolyte;
[0076] (3) The porous Ni obtained in step (1) was used as a working electrode and placed in the electrolyte obtained in step (2) for electroplating, with a silver chloride electrode as a reference electrode and a platinum wire as a counter electrode at 160 mA / cm 2 The electrodeposition was carried out for 480 s at a constant current of , and the obtained product was washed with distilled water several times and dried in a vacuum oven at 30°C to obtain an electrocatalytic material.
[0077] Test Example 1
[0078] The electrocatalytic materials of Examples 1 to 5 and Comparative Examples 1 to 2 were used as working electrodes to test their activity and stability as electrodes for hydrogen production by water electrolysis (HER) and oxygen production (OER) in a three-electrode system, where the electrolyte was 1 M KOH, the counter electrode was a carbon rod, and the reference electrode was a Hg / HgO electrode.
[0079] Before the test, each electrode was activated under the corresponding conditions: the hydrogen production electrode and the oxygen production electrode were subjected to cyclic voltammetry treatment until the current was stable. After pretreatment, the hydrogen production and oxygen production polarization curves of each electrode and the time-current curve at a fixed current density were tested respectively. The current density obtained was 10mA / cm 2 The overpotential required for each electrode is 100mA / cm 2 The overpotential of each electrode after constant current test is shown in Table 1 below:
[0080] Table 1
[0081]
[0082]
[0083] According to the data in Table 1, relative to Comparative Example 1, the electrocatalytic material of the present invention has a low overpotential, a small Tafel slope, a high catalytic activity, and good electrochemical stability when used as a hydrogen production electrode or an oxygen production electrode. Relative to Comparative Example 2, which is only used as an oxygen production electrode, the electrocatalytic material of the present invention has considerable catalytic activity and electrochemical stability when used as an oxygen production electrode. At the same time, the electrocatalytic material of the present invention can also be used as a hydrogen production electrode, and has a low overpotential, a small Tafel slope, a high catalytic activity, and good electrochemical stability. By comparing Example 1 with Example 2 and Example 3, it can be seen that within the mass ratio range of the preferred nickel salt, molybdenum salt, iron salt and complexing agent of the present invention, the catalytic activity of the electrocatalytic material is higher. By comparing Example 1 with Example 4 and Example 5, it can be seen that under the preferred electroplating conditions of the present invention, the catalytic activity of the electrocatalytic material is higher.
[0084] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0085] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0086] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A self-supporting bifunctional electrocatalytic material, characterized in that: The electrocatalytic material comprises a three-dimensional composite material, wherein the three-dimensional composite material comprises a three-dimensional Ni nano-skeleton and a NiMoFe nano-alloy layer coated on the three-dimensional Ni nano-skeleton.
2. The electrocatalytic material according to claim 1, wherein The BET specific surface area of the electrocatalytic material is 2.1 to 2.9 m 2 / g, preferably 2.3 to 2.7 m 2 / g; in the XRD diagram of the electrocatalytic material, there are characteristic peaks at 2θ of 37-40°, 40-43°, 44-47°, 55-60°, 70-74° and 75-80°; XPS measures that the atomic content of Ni element in the electrocatalytic material is 58-84%, the atomic content of Mo element is 9-29%, and the atomic content of Fe element is 4-26%.
3. The electrocatalytic material according to claim 1, wherein The thickness of the NiMoFe nano alloy layer is 10-50 nm.
4. The electrocatalytic material according to claim 1, wherein The electrocatalytic material further comprises a conductive substrate, and the three-dimensional composite material is coated on the conductive substrate; the conductive substrate is a flexible conductive substrate or a hard conductive substrate; The flexible conductive substrate is one of carbon cloth and foam metal; the foam metal is selected from one of foam nickel and foam copper; the hard conductive substrate is one of carbon paper and conductive glass.
5. A method for preparing the electrocatalytic material according to any one of claims 1 to 4, characterized in that: The method includes: S1: mixing nickel salt, molybdenum salt, iron salt and a complexing agent to obtain a mixed solution; adjusting the mixed solution to alkaline using a pH regulator to obtain an electrolyte; S2: Using the three-dimensional Ni nano-skeleton as a working electrode, placing it in the electrolyte obtained in S1, and performing electroplating.
6. The method according to claim 5, wherein: In step S1, the nickel salt is selected from one or more of nickel chloride, nickel sulfate and nickel nitrate, preferably nickel chloride; the molybdenum salt is selected from one or more of sodium molybdate, potassium molybdate and ammonium molybdate, preferably sodium molybdate; the iron salt is selected from one or more of ferrous sulfate and ferrous chloride, preferably ferrous sulfate; the complexing agent is selected from one or more of sodium citrate, potassium citrate, ethylenediaminetetraacetic acid and disodium ethylenediaminetetraacetic acid, preferably sodium citrate.
7. The method according to claim 5, wherein: The mass ratio of the nickel salt, the molybdenum salt, the iron salt and the complexing agent in step S1 is 1: (0.03-0.25): (0.03-0.25): (0.35-1.50), preferably 1: (0.06-0.13): (0.06-0.13): (0.45-0.75); The concentration of the nickel salt is 0.04-0.08 g / ml; the concentration of the molybdenum salt is 0.002-0.01 g / ml; the concentration of the iron salt is 0.002-0.01 g / ml; the concentration of the complexing agent is 0.03-0.06 g / ml; Step S1 also includes using a pH regulator to adjust the pH of the mixed solution to above 9; the pH regulator includes one or more of sodium carbonate, sodium hydroxide and potassium hydroxide, preferably sodium carbonate.
8. The method according to claim 5, wherein: In step S2, the electroplating conditions include: a current density of 50 to 300 mA / cm 2 , preferably 100 to 200 mA / cm 2 ; The electroplating time is 200 to 600 seconds, preferably 300 to 560 seconds; the reference electrode is one or more of a silver chloride electrode, a mercury / mercury oxide electrode and a saturated calomel electrode, preferably a silver chloride electrode; the counter electrode is one or more of a platinum wire and a carbon rod, preferably a platinum wire.
9. The method according to claim 5, wherein: The cross-sectional diameter of the three-dimensional Ni nano-skeleton is 90-120 nm, and the BET specific surface area is 2.7-2.9 m 2 / g; in the XRD pattern of the three-dimensional Ni nanoskeleton, there are characteristic peaks at 2θ of 37-40°, 40-43°, 44-47°, 55-60°, 70-74° and 75-80°.
10. The method according to claim 5, wherein: The three-dimensional Ni nano-skeleton is prepared by the following method: A nickel hydroxide nano-precursor is prepared on a conductive substrate; and the nickel hydroxide nano-precursor is calcined in a reducing atmosphere.
11. The method according to claim 10, wherein: The reducing atmosphere is a mixed gas containing hydrogen and an inert gas; the volume fraction of the hydrogen is 2% to 8%; The calcination conditions include: a calcination temperature of 300 to 500° C. and a calcination time of 0.5 to 2 hours.
12. Use of the electrocatalytic material prepared by the method according to any one of claims 5 to 11 in an oxygen evolution electrode or a hydrogen evolution electrode for water electrolysis.
Citation Information
Patent Citations
NiFeMo ternary electrolytic water electrode and preparation method thereof
CN109811360A
Self-supporting nickel-yttrium oxide electrocatalytic hydrogen evolution electrode and preparation method and application thereof
CN113774419A
Preparation method of nickel-molybdenum-iron electrolyzed water catalyst, obtained product and application
CN115161690A